A view on recent ice-nucleating particle intercomparison studies: why the uncertainty of the activation temperature matters - J. Schrod; H. G. Bingemer (Atmospheric Measurement Techniques)
Ice-nucleating particles (INPs) play a crucial role in cloud formation, influencing cloud phase, lifetime, and the onset of precipitation. Consequently, microphysical processes involving INPs strongly affect the radiative properties of clouds. However, when multiple INP counters are operated simultaneously, notoriously high deviations between instruments in the range of 1 order of magnitude are commonly observed. These differences occur in ambient atmospheric measurements as well as in laboratory studies. A potential reason for these discrepancies that deserves more consideration may be related to uncertainties and errors in the temperature measurement. As the activation of INPs is a strong function of the nucleation conditions, relatively small inaccuracies in the temperature measurement may lead to significant over- or underestimations of the INP concentration. In this study, we have explored this effect as a potential reason for the differences observed among INP counters by analyzing 10 INP intercomparison studies that were published within the last 10 years with a novel quantitative estimate of the temperature uncertainty effect on heterogeneous ice nucleation. The stated temperature uncertainty of instruments used in these experiments ranged from ±0.1 to ±1.5 °C, and was most commonly specified as ±0.5 °C. Potential deviations resulting from typical temperature errors were compared with the reported level of agreement for intercompared methods. As a measure of the potential INP error due to nucleation temperature error, we defined the temperature error factor (TEF) as the quotient of the ice nucleation activity at the actual nucleation temperature divided by the ice nucleation activity at a potentially erroneously measured temperature. Respective TEFs were calculated for five distinct activation spectra based on four INP parameterizations and one compilation of atmospheric INP data. TEFs were between 1.1 and 3.2 for temperature errors of ±0.5 °C, and between less than 2 and larger than 10 for temperature errors of ±1.5 °C. TEFs calculated from parameterizations of aerosols that are highly ice nucleation active were significantly larger than those derived from atmospheric data; although the effect was found to be still as large as a factor of 10 for certain temperature ranges in atmospheric activation spectra at a temperature error of ±2 °C. When comparing two INP instruments, measurement biases may be of opposite direction, thus resulting in expected differences of up to the product of both TEFs. We found that opposite biases of +0.5 and −0.5 °C can therefore typically explain differences of a factor of 2, while opposite biases of +1 and −1 °C can theoretically explain differences of factors up to 5 or even 10, which is of the order of discrepancies typically reported in the literature on INP intercomparisons. These results highlight the need to carefully assess and report on uncertainties of the ice nucleation activation temperature.